Die Alpen im Frühmittelalter Die Geschichte eines Raumes in den Jahren 500 bis 800 - Winckler, Katharina (2012)
This book follows a new path of describing the Alps from the years 500 to 800. Instead of running through this mountain range from east to west (or reverse) and writing one local history after the other, relevant patterns were captured: patterns of control, borders, communication routes, Christendom, settlement, economy, local methods to establish power and traces of local identity. Comparing theses structures on an interregional level made it possible to establish a new view on the early medieval alpine regions. By the year 500 the inhabitants of this central European mountain range were typically roman-provincial. Some regional differences existed, yet the main factors were quite similar: language, laws, religion (Christendom) and social structures. From the 6th c. on this changed. New political developments made a large part of the alpine provinces turn northwards to the Frankish realms. As a consequence borders were created within the Alps. Many hilltop settlements and strongholds in the valleys were built to guarantee the security both of population and borders. Militia was installed to control these boundaries; they were either recruited from the local population or got especially settled for these means. This change of view made some Roman topoi disappear: the Alps were no longer regarded as hostile and as the walls of Italy. The routes through the Alps changed. One reason for this was the growing number of pilgrims from the British Isles made the passage through Maurienne and over the Mont Cenis more important than the ancient route via Montgenèvre. The central Alps in Curia remained a highly important point to cross the mountains, whereas more eastwards the once important crossing points became mere backroads. Farther east the Avarian-Slavic conquest caused the sources to silence, nevertheless the communication routes remained visible through archaeological findings and place names. A big change for the alpine population was the transformations in settlement patterns, first of all the diminishing importance of Roman cities. Some of them disappeared completely, such as Teurnia, Aguntum and Octodurum. Nevertheless, the wider settlement areas around these former towns always remained important. New centres emerged. Some had roman roots, for example Iuvavum/Salzburg, others were new foundations, like the numerous cloisters from the 8th c. The church played a significant role in this transformation, as a bishop's see or the burial church of a saint constituted a point of attraction for the local population. The antique transalpine and alpine networks of trade underwent some transitions. Goods like olive oil, high quality pottery and sea salt were no longer brought over the Alps. The eastern alpine ore deposits were not exploited on a grand scale anymore. New natural resources became important, for example the salt deposits in the northern Alps. There are some traces of exported products. The vineyards of the Southern Alps produced vine for export to the north-alpine regions and the central alpine soapstone production supplied the population of the whole mountain range with high quality cookware. In addition to this, products like cheese, wool, honey and lumber might have been exported. Alpine agriculture did not change much. Farming was based on subsistence and the surplus was sold locally to travellers or given to the owners of the land. The use of alpine pastures roots in pre-roman times and was practised continually, although the intensity of the pastoralism is difficult to estimate. Local power structures emerged out of late antique roots. In the 8th and beginning of the 9th c. the population of these parts of the Alps still spoke a roman language, were Christian and lived in a very differentiated social structure whose legal habits were based on roman law. Contrary to that, the eastern Alps saw a major cultural shift that resulted in the Slavic reign of Carantania.